2021
DOI: 10.1016/j.ebiom.2021.103502
|View full text |Cite
|
Sign up to set email alerts
|

A dried blood spot protocol for high throughput analysis of SARS-CoV-2 serology based on the Roche Elecsys anti-N assay

Abstract: Background Since 2020 SARS-CoV-2 spreads pandemically, infecting more than 119 million people, causing >2·6 million fatalities. Symptoms of SARS-CoV-2 infection vary greatly, ranging from asymptomatic to fatal. Different populations react differently to the disease, making it very hard to track the spread of the infection in a population. Measuring specific anti-SARS-CoV-2 antibodies is an important tool to assess the spread of the infection or successful vaccinations. To achieve sufficient sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…We previously showed a high sensitivity and specificity of the Elecsys ® Anti-SARS-CoV-2 assay (Roche) used in this sero-study [ 5 ]. For the follow-up, we developed and carefully validated a semi-automated protocol using self-sampled DBS for SARS-CoV-2 serology [ 7 ]. This approach facilitates field work to a very considerable extent and thus, makes studies with a higher frequency of follow-ups more feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed a high sensitivity and specificity of the Elecsys ® Anti-SARS-CoV-2 assay (Roche) used in this sero-study [ 5 ]. For the follow-up, we developed and carefully validated a semi-automated protocol using self-sampled DBS for SARS-CoV-2 serology [ 7 ]. This approach facilitates field work to a very considerable extent and thus, makes studies with a higher frequency of follow-ups more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to full blood samples, sensitivity of the DBS method was 99.2% and specificity 98.7%. Details of the laboratory methods are described in [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the DABA, the absence of normal levels of serum protein in the first incubation would be expected to increase the off-rate during antibody binding, substantially reducing sensitivity as we observed. We note with interest the recent publication by Beyerl et al, who described a sensitivity of 99.2% using the Roche DABA assay, achieved by a substantial redesign of the assay cut-off for DBS eluates 27 .…”
Section: Discussionmentioning
confidence: 92%
“…If necessary, the sensitivity of DBS analysis with the Elecsys anti-SARS-CoV-2 S assay could be improved by working with other instruments to enable the use of lower volumes. Recent work showed that a 60 µL volume was sufficient with a Cobas e801 to work with DBS [22]. The initial volume of dried blood could also be increased by using other quantitative/volumetric DBS specimens allowing collection of 20 µL or 30 µL per spot (e.g., Tasso M-20 from TASSO Inc., Mitra from Neoteryx).…”
Section: Discussionmentioning
confidence: 99%
“…DBS by finger prick is well tolerated, and auto-sampling worked well with our cohort of volunteers. Beyerl et al performed high-scale monitoring of anti-SARS-CoV-2 antibodies in volunteers with DBS and reported that 4465/4471 of unsupervised home sampling DBS cards (99.87%) could be analyzed [22], thus showing that it is a viable strategy to obtain samples even from untrained individuals. The DBS device used in this study was also successfully used in a large test of auto-sample collection evaluation in Stockholm (878 individual Capitainer cards).…”
Section: Discussionmentioning
confidence: 99%